Estudo anatomopatológico da Valva Mitral acometida pela Doença Reumática - Nayana Flamini Arantes Gomes (2017)
The underlying mechanisms by which rheumatic heart disease (RHD) lead to severe valve dysfunction are not completely understood. Histological analysis of mitral valves excised from RHD patients are of great importance to define strategies that prevent disease progression. The present study was designed to comprehensively evaluate the histopathological changes in mitral valves at an end stage of valve dysfunction, seeking an association between the pattern of predominant valvular dysfunction and histopathological findings. Sixty mitral valves were collected from patients undergoing valve replacement, 40 were from RHD patients and 20 from controls undergoing heart transplantation. Clinical and echocardiographic data were collected from RHD patients. Histological analyses were performed using Hematoxylin-eosin staining to determine the degree of inflammation and fibrosis in the endocardium and interstitium, the presence of neoangiogenesis, calcification and adipose metaplasia. The mean age of RHD patients was 53 ± 13 years, 36 (90%) were female, whereas mean age of controls was 50 ± 12 years, similar to the cases, with the majority of males (70%). The rheumatic valve endocardium presented greater thickness than the controls (1.3 ± 0.5 mm versus 0.90 ± 0.4 mm, p = 0.003, respectively) and a more intense inflammatory infiltrate in the endocardium (78% versus 36%; p = 0.004), with predominance of mononuclear cells. Fibrosis occurred in all rheumatic and control valves, but with a higher intensity in rheumatic valves (100% vs 29%, p <0.001). Calcification occurred in 35% of rheumatic valves, especially among stenotic valves compared to regurgitation or combined lesions (56% versus 18%, p = 0.014, respectively). An active inflammatory process was present in rheumatic mitral valve end-stage lesions, with mild intensity, focal distribution and with predominance of mononuclear cells. Severe fibrosis was found in the interstitium of all rheumatic valves leading to valve deformity and dysfunction during advanced disease. Valvular calcification was more frequent in mitral stenosis, associated with mitral valve area, indicating advanced rheumatic involvement.